Financial Distress and Tax Avoidance: The Role of ESG as an Ethical Safeguard in Emerging Markets - Lusi Andriyana; Alfa Rahmiati; Heru Tjaraka (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to examine the effect of financial distress on tax avoidance and the moderating role of Environmental, Social, and Governance (ESG) in non-financial companies listed on the Indonesia Stock Exchange during the 2019-2023 period. Tax avoidance is measured using the Current Effective Tax Rate (CETR), financial distress is proxied by the Altman Z-score, and ESG is measured using Bloomberg ESG Disclosure Scores. This study applies a quantitative approach using panel data regression and firm size as a control variable. The results show that financial distress has a positive and significant effect on tax avoidance, indicating that financially pressured firms tend to reduce tax burdens to preserve cash flow. However, ESG does not significantly moderate this relationship, although the interaction coefficient is negative as theoretically expected. This study contributes to the literature by integrating financial risk, governance, and sustainability perspectives in the context of post-pandemic corporate behavior in emerging markets.